INVESTASI DANA WAKAF - Nurma, Nurma (The Pontianak State Institute of Islamic Studies, 2013)
Three basic principles that should be emphasized when we want to apply the principle of cash waqaf (endowment): first, the allocation of waqaf should be viewed as a frame of the integrated project, not part of a separate fee. Second, the hope and welfare of nazir; it's time we made the nazir a profession that gives hope to the best graduate and a profession that provides welfare. Third, the principles of transparency and accountability in which the waqaf agency and the institutions receiving endowments must report the fund management process to the people annually in the form of financial audit report, including the reasonableness of the cost of each item.